Photon Blockade via Frequency Chirped Excitations - G. H. Hovsepyan
Frequency-chirped systems have attracted widely attentions in both experiments and theory that is motivated by both testing of quantum optics theory and engineering new devices. In this report, we propose to use the frequency-chirped excitations for realizing effective mechanism of Photon Blockade.
Keywords: Physics; Optics